Serum macrophage-derived chemokine and interleukin 18 concentrations are associated with disease severity in children with atopic dermatitis. - Wrzask, M.; Machura, E.; Mazur, B.; Chrobak, E.; Ziora, K. (European Journal of Pediatric Dermatology, 2015)
In the pathogenesis of AD, immunological disturbances play a central role. Immune dysregulation in AD includes increased production of inflammatory cytokines, elevated serum immunoglobulin E (IgE) levels and inflammatory cell infiltration. Defects in the innate and adaptive immune responses as well as T cell disturbances lead to and sustain allergic inflammation. Macrophage-derived chemokine (MDC/CCL22) and interleukin (IL)-18 are elements of both innate and adaptive immune responses whose role in the development of skin lesions is widely discussed. Serum MDC and IL-18 levels were assessed in 60 AD children (mean age 8.1 years) and 40 healthy controls (mean age 9.62 years) to investigate a possible associations between MDC and IL-18 concentrations and the clinical severity of the disease. The children were divided into two age groups (< 7 years old and ≥ 7 years old). We compared these groups for serum levels of MDC, IL-18, total IgE and blood eosinophils and analyzed their correlation with the severity of skin lesions, defined by the scoring atopic dermatitis (SCORAD) index. The serum concentrations of MDC and IL-18 in AD patients were significantly higher than in healthy controls. The serum MDC levels significantly correlated with the SCORAD and other markers of allergic inflammation such as total IgE and eosinophil count in peripheral blood in both age groups. Serum IL-18 levels correlated positively with SCORAD index in the young children. In conclusion MDC and IL-18 serum concentrations may be useful inflammatory markers for assessing AD severity in children.